Analysis of Recreational Sports on Intrinsic Motivation to Write a Thesis in Final Semester Sports Science Students - Amirul Rosyid; Sahri Sahri (Borong Newinera Publisher, 2026)
This study aims to examine the relationship between recreational exercise and intrinsic motivation in final year students of the Sport Science Study Program, Semarang State University, class of 2022, in completing their theses. Using a quantitative correlational approach with a descriptive design, a sample of 23 students was drawn through purposive sampling, and data were collected via the IPAQ short form questionnaire for physical activity and the IMI for intrinsic motivation. Analysis included normality, linearity, and Spearman correlation tests using SPSS 26. The results showed a